Enhanced catalytic palladium embedded inside porous silicon for improved hydrogen gas sensing - Alhan Farhanah Abd Rahim,; Nurul Syuhadah Mohd Razali,; Rosfariza Radzali,; Ainokhilah Mahmood,; Irni Hamiza Hamzah,; Mohamed Fauzi Packeer Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this work, we reported on room temperature porous silicon (PS) and embedding PS using simple and economical techniques of electrochemical etching and thermal evaporation. The PS substrate was prepared using the technique of electrochemically etching the n-type Si (100) wafer at a constant current density of 10 mA/cm2 for 10 min under the illumination of incandescent white light. After PS formation, Ge pieces were thermally evaporated onto the two PS substrates in a vacuum condition. This was then followed by the deposition of the ZnO layer onto the Ge/PS substrate by the same method using commercial 99.9% pure ZnO powders. The three samples were identified as PS, Ge/PS and ZnO/Ge/PS samples, respectively. Pd finger contacts were deposited on the PS and embedding PS (Ge/PS and ZnO/Ge/PS) to form Pd on PS hydrogen sensors using RF magnetron sputtering. SEM and EDX suggested the presence of substantial Ge and ZnO inside the uniform circular pores for Ge/PS and ZnO/Ge/PS samples, respectively. Raman spectra showed that good crystalline Ge and ZnO nanostructures embedded inside the pores were obtained. For hydrogen sensing, Pd on ZnO/Ge/PS Schottky diode exhibited a dramatic change of current after exposure to H2 as compared to PS and Ge/PS devices. It is observed that the sensitivity increased exponentially with the hydrogen flow rate for all the sensors. The ZnO/Ge/PS showed more sensitivity towards H2 than that of PS and Ge/PS especially at high flow rate of H2 with higher current gain (69.11) and shorter response (180 s) and recovery times (30 s).